2003
DOI: 10.1080/0042098032000116121
|View full text |Cite
|
Sign up to set email alerts
|

Rent-seeking Behaviour and its Economic Costs in Urban Land Transactions in Accra, Ghana

Abstract: The existing body of knowledge attributes to informal land transactions in sub-Saharan African cities observed problems in city neighbourhoods. Substantial resources, often backed by donor agencies, are therefore being spent in revamping bureaux and governmental bodies in a bid to solve the problems. This paper examines the economic impacts of this aspect of market intervention. Employing insights from rent-seeking theory, it estimates costs brought to bear on agents by government agencies' involvement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…The state defines these transactions as land leases, and the 1992 Constitution prohibits the creation of freehold interests in customary land and only allows for land leases. However, a normative structure for leases does not exist in practice (Antwi and Adams 2003), and most buyers are not clear about what will happen when their leases expire. Gough and Yankson (2000) found that only 25 per cent of land purchasing households they interviewed had paid ground rent to the municipal authority.…”
Section: Real Estate: Urban and Peri-urban Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The state defines these transactions as land leases, and the 1992 Constitution prohibits the creation of freehold interests in customary land and only allows for land leases. However, a normative structure for leases does not exist in practice (Antwi and Adams 2003), and most buyers are not clear about what will happen when their leases expire. Gough and Yankson (2000) found that only 25 per cent of land purchasing households they interviewed had paid ground rent to the municipal authority.…”
Section: Real Estate: Urban and Peri-urban Areasmentioning
confidence: 99%
“…In a survey conducted in 1995/6 of 233 land-purchasing households within peri-urban Accra, Gough and Yankson (2000) found that 60 per cent of the sample had not registered their land because they considered it too difficult or unnecessary. In a survey conducted in 1999 of 286 land-purchasing households in Accra, Antwi and Adams (2003) found that nearly 78 per cent of the sample had not formally registered their land. A considerable proportion of those with registered plots had spent more than five years to get land titles.…”
Section: Contemporary Land Reform Initiatives In An Era Of Neo-liberamentioning
confidence: 99%
“…Antwi and Adams (2003) found that when resources from outside sources designed for the projects of urban renewal are diverted by government agencies via privileges and high salaries for administrators, few funds accomplish their intended use. Another study done by Mbaku (1999) reported that politics and the structure of the institutions in African countries enhance rent-seeking behaviour by assigning a large number of restrictions on regular economic activities.…”
Section: The Impact Of Corruption On Economic Growth (Gdp)mentioning
confidence: 99%
“…Thus, it is argued that by strengthening the position of customary land authorities and building their capacities to manage land and document transactions, customary transactions will be increasingly documented and made transparent. This will prevent corruption in both customary and bureaucratic sectors (Antwi and Adams 2003;Toulmin and Quan 2000b).…”
Section: Kojo Amanormentioning
confidence: 99%
“…In Ghana the customary sector holds around 80 per cent of the land (Antwi andAdams 2003, Kasanga andKotey 2001). This sector thus provides land for the residential and other economic activities of most of Ghana's citizens.…”
Section: The Nature Of Landholding In Ghanamentioning
confidence: 99%